The Correlation of Academic Stress to Smartphone Addiction on Medical Faculty Students of Nusa Cendana University - Cahya Ayu Ningsih; Cahya, S., Rr., Ayu, S.M, Listyawati Ningsih, Koamesah, Nurina (Universitas Nusa Cendana, 2025)
Background : One of the factors that influence smartphone addiction is situational factors such as academic stress. Medical students have higher levels of stress than other faculties, due to having additional stress as a result of longer study periods and applying different curriculum. Person experiencing stressful situations will naturally attempt to overcome them by using a certain number of behaviors, one of which is by playing a smartphone. Objective : To find out relation beetween academic stress levels to smartphone addiction in medical students of Nusa Cendana University. Methods : This study was an observational analytical research with cross sectional design conducted on medical students of Nusa Cendana University by filling out the Medical Student Stressor Questionnaire (MSSQ) questionnaire and smartphone addiction scale short version (SAS-SV) questionnaire. The sampling technique uses stratified random sampling with 67 respondents fulfilling the inclusion and exclusion criteria. The study was conducted univariate, bivariate using the chi-square test. Results : From 67 respondents, 1 (1.5%) respondents experienced mild academic stress, 27(40.3%) moderate stress respondents, 29 (43.3%) respondents were severely stressed and 10 (14.9%) respondents are very severely stressed. Of the 67 respondents also obtained 44 (65.7%) respondents addicted to smartphones and 23 (34.3%) respondents not experience smartphone addiction. The results of bivariate analysis test in this study obtained the result of p=0.588 (p>0.05). Conclusion : There is no relationship between academic stress and smartphone addiction in medical students of Nusa Cendana University